(3MGTjI aj GdefWbs - (3ejQRGLGfs
(3ChdgG (B:s
(3bGd GdeUfa QMeg Gddg CeG HYO MeO hGLH GdhLhO Ydi fYeGFg ai JQc GdehUha s
(3BNQgG (B:s
(3aeG PcQg MjK aSQ eYfi GdCUd djS OaYkG dgPG GdOhQ Hd cGf dCf jbhd gPG GdbjO djS LRA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs